Understanding the Limitations of Maastricht - Daniel Gros (Intereconomics, 2019)
The unspoken, implicit assumption was that financial instability can only arise alongside inflation and that the stability of financial markets should remain a national task. Both of the latter assumptions turned out to be untenable.
Keywords: 330